PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL DRILLING UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN REAKSI REDUKSI OKSIDASI DI KELAS X SMA HANDAYANI PEKANBARU - Yusnia Anggari Anggari; R Usman Rery Rery; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to increase student achievementon the subject Oxidation Reduction Reaction inclass X SMA Handayani Pekanbaru. This research is a kind of experiment research with pretest-posttest design. The research was conducted in SMA Handayani Pekanbaru..The samples of this research were the students of class X MIA 3 as the experimental class and students of class X MIA 1 as the control class. Experimental class is a class that is cooperative learning model Snowball Drilling, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic> ttable is 2,2104 > 1,67, means that the application of cooperative learning model Snowball Drilling can improve student achievement on the subject of Oxidation Reduction Reaction class X SMA Handayani Pekanbaru increase learning achievement category in the experimental class is based on the normalized gain scores (N-Gain) relatively high at 0,7493. Key words : Cooperative Learning, Snowball Drilling, Learning Achievement, Oxidation Reduction Reaction